Artificial intelligence, tasks, skills and wages: Worker-level evidence from Germany - Erik Engberg; Michael Koch; Magnus Lodefalk; Sarah Schroeder (Örebro University School of Business, 2023)
This paper documents novel facts on within-occupation task and skill changes over the past two decades in Germany. In a second step, it reveals a distinct relationship between occupational work content and exposure to artificial intelligence (AI) and automation (robots). Workers in occupations with high AI exposure, perform different activities and face different skill requirements, compared to workers in occupations exposed to robots. In a third step, the study uses individual labour market biographies to investigate the impact on wages between 2010 and 2017. Results indicate a wage growth premium in occupations more exposed to AI, contrasting with a wage growth discount in occupations exposed to robots. Finally, the study further explores the dynamic influence of AI exposure on individual wages over time, uncovering positive associations with wages, with nuanced variations across occupational groups.
Keywords: J23; J24; J44; N34; O33; 330; Artificial intelligence technologies; Task content; Skills; Wages